A mitochondrial genetic divergence proxy predicts the reproductive compatibility of mammalian hybrids. Issue 1928 (10th June 2020) - Allen, Richard; Ryan, Hannah; Davis, Brian W.; King, Charlotte; Frantz, Laurent; Irving-Pease, Evan; Barnett, Ross; Linderholm, Anna; Loog, Liisa; Haile, James; Lebrasseur, Ophélie; White, Mark; et al.
Abstract : Numerous pairs of evolutionarily divergent mammalian species have been shown to produce hybrid offspring. In some cases, F1 hybrids are able to produce F2 s through matings with F1 s. In other instances, the hybrids are only able to produce offspring themselves through backcrosses with a parent species owing to unisexual sterility (Haldane's Rule). Here, we explicitly tested whether genetic distance, computed from mitochondrial and nuclear genes, can be used as a proxy to predict the relative fertility of the hybrid offspring resulting from matings between species of terrestrial mammals. We assessed the proxy's predictive power using a well-characterized felid hybrid system, and applied it to modern and ancient hominins. Our results revealed a small overlap in mitochondrial genetic distance values that distinguish species pairs whose calculated distances fall within two categories: those whose hybrid offspring follow Haldane's Rule, and those whose hybrid F1 offspring can produce F2 s. The strong correlation between genetic distance and hybrid fertility demonstrated here suggests that this proxy can be employed to predict whether the hybrid offspring of two mammalian species will follow Haldane's Rule.